SOLUSI PERIODIK DARI PERSAMAAN KORTEWEG de VRIES (KdV) DENGAN OPERATOR BILINIER HIROTA - Rubiyanti, Sri; Sutimin, Sutimin (JURNAL SAINS DAN MATEMATIKA, 2010)
Abstract. Hirota bilinear  operator  (Hirota Method) is proposed  to directly construct periodic wave solutions from Korteweg de Vries (KdV)  equation.  This solution can be expressed  in terms of  Jacobi  Theta 4 (Θ4)  functions, with  dispersion  relation  yielded  from  degradation of  biliear  equation. Then,  sinusoidal wave,  Solitary,  and Cnoidal can  be  reduced  from this solution to asses  certain of nome  (q).Key words: Hirota Bilinear operator,  Korteweg  de Vries  (KdV) equation,  periodic profil  gelombang  khusus seperti gelombangCnoidal  dan  Solitary.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/2962